2009
DOI: 10.2106/jbjs.h.01075
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Midfoot Instability in the Subtle Lisfranc Injury

Abstract: Magnetic resonance imaging is accurate for detecting traumatic injury of the Lisfranc ligament and for predicting Lisfranc joint complex instability when the plantar Lisfranc ligament bundle is used as a predictor. Rupture or grade-2 sprain of the plantar ligament between the first cuneiform and the bases of the second and third metatarsals is highly suggestive of an unstable midfoot, for which surgical stabilization has been recommended. The appearance of a normal ligament is suggestive of a stable midfoot, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Longitudinal instability required sectioning of both the interosseous first cuneiform, second metatarsal ligament and the interosseous ligament between the first and second cuneiforms. Raikin et al[ 21 ] pointed out in research on the Lisfranc injuries of American football players that rupture or grade-2 sprain of pC1-M2M3 is highly suggestive of an unstable midfoot, for which surgical stabilization is recommended. The appearance of a normal ligament is suggestive of a stable midfoot and the documentation of its integrity may obviate the need for a manual stress radiographic evaluation under anesthesia for a patient with equivocal clinical and radiographic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal instability required sectioning of both the interosseous first cuneiform, second metatarsal ligament and the interosseous ligament between the first and second cuneiforms. Raikin et al[ 21 ] pointed out in research on the Lisfranc injuries of American football players that rupture or grade-2 sprain of pC1-M2M3 is highly suggestive of an unstable midfoot, for which surgical stabilization is recommended. The appearance of a normal ligament is suggestive of a stable midfoot and the documentation of its integrity may obviate the need for a manual stress radiographic evaluation under anesthesia for a patient with equivocal clinical and radiographic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant limitation to determining the diagnostic accuracy of any imaging modality is the lack of a non‐invasive gold‐standard diagnostic test from which to calculate specificity and sensitivity. Surgical findings of disruption or instability are often used as a reference standard for diagnosis . Considering that a significant proportion of LF injuries are treated non‐operatively it is not possible to determine the accuracy of this diagnosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical findings of disruption or instability are often used as a reference standard for diagnosis. 7,12,13 Considering that a significant proportion of LF injuries are treated non-operatively it is not possible to determine the accuracy of this diagnosis in these patients.…”
Section: Limitationsmentioning
confidence: 99%
“…Potter et al 27 established the utility of MRI for the assessment of Lisfranc injury in a series of athletes who had sustained acute midfoot injuries, demonstrating high accuracy upon radiographic and surgical correlation and confirming prior reports that the weaker dorsal fibers of the ligament are more commonly torn than the more robust plantar fibers in the setting of partial thickness injury (Figure 4B and 4C). 24 Raikin et al 29 demonstrated that disruption of the plantar fibers of the Lisfranc ligament on imaging provides a predictor of Lisfranc joint instability, with a positive predictive value of 94%, allowing accurate determination of the need for surgical intervention.…”
Section: Pathologymentioning
confidence: 99%
“…1,6,29 Such injuries account for approximately 2% to 18% of athletic injuries, depending on the type of activity, with sports involving running, jumping, and contact resulting in greater risk of injury. Foot injuries constitute approximately 2% of football, basketball, and women’s soccer injuries; 4% of men’s soccer injuries; and up to 18% of martial arts injuries.…”
mentioning
confidence: 99%